Analisis Partisipasi Masyarakat Pada Kawasan Ekowisata Mangrove Di Kelurahan Lubuk Kertang Kabupaten Langkat - Sari, Novita (JURNAL AGRICA, 2024)
The condition of Lubuk Kertang's mangrove forests and ecotourism has decreased. This is based on the lack of community role and the lack of government role in preserving Lubuk Kertang mangrove ecotourism. The aim of this research is to analyze community participation in the mangrove ecotourism area in Lubuk Kertang sub-district, Langkat district. This research took place at Mangrove Ecotourism located in Lubuk Kertang Village, Pangakalan Susu District, Langkat Regency. The population in this research is the entire surrounding community, totaling 1124 heads of families and the samples in this research are 32 people from the sustainable mangrove group which specializes in the Lubuk Kertang Ecotourism sector and 122 people from the blooming mangrove group which specializes in preserving the Lubuk Kertang Mangrove forest. The data analysis used in this research is multiple linear regression analysis. The results of the research partially show that community needs, community requests, community customs and regulations have an influence on community participation in Lubuk Kertang Village. In this way, people who depend on ecotourism will increase their level of participation in managing and caring for Lubuk Kertang mangrove ecotourism.